Implementasi Program Kampus Mengajar di Desa Budo Kecamatan Wori Kabupaten Minahasa Utara: Implementation of the Kampus Mengajar Program in Budo Village, Wori District, North Minahasa Regency (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
The lack of teachers and limited educational resources in Budo Village, Wori District, Minahasa Regency, poses significant barriers to improving the quality of education. This community service program aims to implement the Kampus Mengajar initiative at SD GMIM Budo as a partner school, involving students from the Integrated Community Service (KKT) program according to the implementation guidelines from the Sam Ratulangi university. The synergy of  this program provides practical teaching experience for KKT students, allowing them to directly contribute to the partner school through additional work programs. The benefits of this program include improving the quality of teaching at elementary schools, developing teaching and leadership skills among students, and increasing the involvement and contribution of lecturers and students in community empowerment. The implementation of the Kampus Mengajar involving KKT students in partner villages has a positive impact on addressing the shortage of teachers and offers valuable experiences for students in developing professional skills and contributing to the community.